Protection of abused and neglected children: comparison study of laws in Malaysia & United Kingdom / Noor Hidayah Yahaya … [et al.] - Yahaya, Noor Hidayah; Abd Kamal, Fatin Ajlaa; Mohamed Jamal, Siti Fitrah; Kamaruddin, Wan Aminatul Aisyah (2011)
Child abuse and neglect is a growing problem in both Malaysia and the United Kingdom. There are numerous cases regarding this matter in both countries calling for the public's sympathy. One of the issues on this matter is the lack of definition on what is physical and mental abuse in the Malaysian act as compared to its UK's counterpart. As compared to the United Kingdom, the Children Act is serving its purpose in prosecuting the perpetrators. Consequently, the Malaysian act is also silent on the post-trial custody of the child. This study intends to examine the protection given to a child who is physically and mentally abuse as well as to analyse the different approaches used by the two countries in handling this issue. Authors in their writings are of the opinion that child abuse and neglect has to be defined on a case to case basis. Malaysian authors are mainly concerned on the admissibility of evidence provided by a child witness as well as the whole trial procedure. This study however intends to fill the loopholes and inadequacies of Child Act 2001, by comparing it and to propose some amendments of the Child Act 2001.